Autophagy in Negative-Strand RNA Virus Infection - Wang, Yupeng; Jiang, Ke; Zhang, Quan; Meng, Songshu; Ding, Chan (Frontiers in Microbiology, 2018)
Autophagy is a homoeostatic process by which cytoplasmic material is targeted for degradation by the cell. Viruses have learned to manipulate the autophagic pathway to ensure their own replication and survival. Although much progress has been achieved in dissecting the interplay between viruses and cellular autophagic machinery, it is not well understood how the cellular autophagic pathway is utilized by viruses and manipulated to their own advantage. In this review, we briefly introduce autophagy, viral xenophagy and the interaction among autophagy, virus and immune response, then focus on the interplay between NS-RNA viruses and autophagy during virus infection. We have selected some exemplary NS-RNA viruses and will describe how these NS-RNA viruses regulate autophagy and the role of autophagy in NS-RNA viral replication and in immune responses to virus infection. We also review recent advances in understanding how NS-RNA viral proteins perturb autophagy and how autophagy-related proteins contribute to NS-RNA virus replication, pathogenesis and antiviral immunity.